EVALUASI KINERJA STASIUN KERETA API BERDASARKAN STANDAR PELAYANAN MINIMUM (Studi Kasus: Stasiun Tugu dan Stasiun Lempuyangan Yogyakarta) - , RISNA RISMIANA SARI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Station is one of the infrastructures to support a train journey in which there is interaction between providers and users. In operation, service providers must be able to provide good service to users. Therefore, analysis of the various facilities service standards required by the concept of movement of the user is needed. Standard-setting begins with the direct analysis of the needs of the facilities at the station based on the patterns of movement and user requests regarding the ease, convenience, security and safety. From the analysis of the extent to which the formulation is obtained minimum service standards set out in the Minister of Transportation Regulation Number: PM 9 Year 2011 on Minimum Service Standard for People with Railway Transport, in particular regarding the service at the station to facilitate the user's needs and then provide recommendations on standards of care stations to better performance. Minimum service standards are based on the completeness and performance facilities. Based on the preparation of minimum service standards, minimal parking available land area is 3.5 to 7.5 SRP / floor area of an effective, long service counters up to 2 minutes per subscriber, per passenger space in the waiting room of at least 0.6 m 2 , the number of toilets minimum for each of the men and women is 6 normal and 2 persons with disabilities at a large station, 4 normal and 1 (one) at the station are disabled, 2 normal and 1 (one) people with disabilities at a small station with a minimum dimension of 750x1350 mm, places of worship in the area of the station is able to accommodate a minimum of men and women respectively 4 people or each accommodate 10 people for a solid station, the maximum ramp slope of 20% for the ease with disabilities, the number, length and width of the platform adapted to the length of the circuit that operates passenger trains and passenger numbers during peak hours as well as many other value added performance to provide better service.